PENINGKATAN MINAT DAN HASIL BELAJAR SISWA MENGGUNAKAN MEDIA GAME BELAJAR BANGUN DATAR (LABADA) BERBANTUAN METODE TGT PADA PEMBELAJARAN MATEMATIKA KELAS V DI SEKOLAH DASAR - Isnaini Aprodita Putri Alansyah; Ida Putri Rarasati; Devita Sulistiana (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
Based on preliminary analysis, it was found that low interest in learning and lack of understanding of students in learning due to limited use of technology-based media can cause a decrease in student learning outcomes. This study aims to explain the increase in interest and learning outcomes of students using flat building learning game media (LABADA) assisted by the TGT method in fifth grade mathematics learning in elementary schools. This study is a quasi-experimental study with a pretest-posttest non-equivalent control group design, with a sample of 56 fifth grade students of UPT SDN Srengat 01, 28 students in class VA and 28 students in class VB. The results of the T Test showed that there was an influence between variable X and Y1, with a t count of 2.142 > t table 2.056 and a Sig. value of 0.042 < 0.05, and there was an influence between variable X and Y2, with a t count of 2.413> t table 2.056 with a Sig. value of 0.023 < 0.05. The results of the MANOVA test show that there is an influence between variable X on variables Y1 and Y2, with the obtained f-value of interest 22.863 > f-table 4.21 with Sig. 0.000 < 0.05, and f-value of learning outcomes 84.419 > f-table 4.21 with Sig. 0.000 < 0.05. From this study, it can be concluded that there is an increase in students' interest and learning outcomes using the LABADA game media assisted by the TGT method in mathematics learning for grade V of elementary school.